Cobalt‐Catalyzed Electrophilic Amination of Arylzincs with N‐Chloroamines. Issue 20 (22nd March 2013) - Qian, Xin; Yu, Zailu; Auffrant, Audrey; Gosmini, Corinne
<x xml:space="preserve">Abstract</x> Roles reversed: An efficient cobalt‐catalyzed electrophilic amination of arylzinc reagents has been achieved. A variety of functionalized arylzincs and N‐chloroamines were coupled under mild conditions (see scheme). Both secondary and tertiary arylamines were obtained in moderate to excellent yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>